Animal Protection in the New Croatian Criminal Law - Vuletić, Igor (Glasnik Advokatske komore Vojvodine, 2025)
This paper provides a concise overview of the criminal offenses concerning animal protection in Croatian criminal law. It examines the offense of killing or abuse of animals (Art. 205) and the newly introduced offense of animal abandonment (Art. 205a). The paper outlines the statutory elements of criminal liability, surveys the available case-law, and discusses related practical issues. Its value lies in being the first work in the literature to analyze the new offense of animal abandonment. The offense is compared with the established offense of killing and abuse of animals, and the rationale for its introduction is critically assessed. The author argues that the amendment has created legal uncertainty and was unnecessary, as animal abandonment was already sufficiently covered by the offense of killing and abuse of animals.
Keywords: animal; killing; abuse; abandonment; intent; negligence; suspended sentence